Biochar tablets with and without embedded fertilizer on the soil chemical characteristics and nutrient use efficiency of zea mays - Yit, Leng Lee; Ahmed, Osumanu Haruna; Abdul Wahid, Samsuri; Ab Aziz, Zakry Fitri (MDPI, 2021)
Densification of ashy biochar into tablet can enhance the handling and conveyance efficiencies of biochar. It was hypothesized that fertilizer-embedded biochar tablets can slowly release embedded nutrients in synchrony with optimum nutrient uptake by crops. The objectives of this research were to determine the effects of biochar tablets with and without embedded fertilizer on soil chemical properties and nutrient use efficiency of Zea mays (sweet corn). The biochar tablet (BT) was produced by blending a biochar mixture with starch followed by densification using a single punch tablet press whereas the fertilizer embedded biochar tablet (BF) was prepared using the same procedure except that NPK fertilizer was added during blending. A pot experiment with five fertilization treatments including control was carried out in an open field located in Perlis, Malaysia. Co-application of biochar and fertilizer increased soil total carbon, nitrogen, but it reduced soil electrical conductivity (EC). Additionally, the BF significantly increased leaf chlorophyll content, dry root weight, and total plant nutrient use efficiency of sweet corn. The findings suggest that BF can serve as a slow release fertilizer to improve crop nutrient use efficiency. Therefore, embedding fertilizer in biochar tablets is recommended for sweet corn production following a long term field study to confirm the findings of this pot study.